2007
DOI: 10.2174/157488607779315516
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Adverse Drug Reactions: A Review of Literature and Data from ADR Spontaneous Reporting Databases

Abstract: The musculoskeletal system can be a target organ for adverse drug reactions (ADRs). Drug-induced muscle, bone or connective tissue injuries may be due to, i), primary direct drug action, or, ii), undirected consequence of generalized drug-induced disease. Musculoskeletal ADRs may be only temporarily disabling, such as muscle cramps, as well as in other cases may be serious and life-threatening, such as rhabdomyolysis. In the last few years there has been an increasing awareness of musculoskeletal ADRs. Some re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 213 publications
(185 reference statements)
0
12
0
Order By: Relevance
“…Our data also demonstrated that miR-367 was involved in ADR-induced apoptosis in OS cells. ADR is a kind of chemotherapeutic drug applied in kinds of malignant cancers [27] , [28] . ADR induced OS cells apoptosis, meanwhile, decreased the expression of miR-367.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also demonstrated that miR-367 was involved in ADR-induced apoptosis in OS cells. ADR is a kind of chemotherapeutic drug applied in kinds of malignant cancers [27] , [28] . ADR induced OS cells apoptosis, meanwhile, decreased the expression of miR-367.…”
Section: Discussionmentioning
confidence: 99%
“…Recently discovered deleterious effects of drugs on the ECM are tendinopathies associated with the use of statins (Marie et al, 2008) and fluoroquinolones (Conforti et al, 2007). Furthermore, skeletal consequences (particularly increased risk of bone fractures in the appendicular skeleton in women with type 2 diabetes, caused by thiazolidinediones, an antidiabetic drug class) has been noticed (Grey, 2008).…”
Section: Deleterious Effects Of Current Drugs On the Extracellularmentioning
confidence: 99%
“…These differences in the type of ADRs for conventional and atypical antipsychotics are globally consistent with results from the literature. [23][24][25][26][27][28][29][30] The association of antihypertensive drugs with SADRs seemed to be more important for autonomic nervous and vascular extra-cardiac ADRs than for other types of ADRs, which was not surprising as both these categories include hypotension ADRs. Even so, the use of antihypertensive drugs was associated with a 2-fold increase in the rate of reporting of CNS, gastrointestinal and heart rate and rhythm SADRs, very similar to the global increase in the risk of seriousness estimated for all ADRs in antihypertensive drug users.…”
Section: Discussionmentioning
confidence: 99%